Pengaruh Work Life Balance Terhadap Kinerja Karyawan Yang Dimediasi Oleh Komitmen Organisasi Karyawan Pada PT. BPR Santi Pala (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
The high number of financial institution developments has become fierce competition between fellow competitors, one of which is PT. BPR Santi Pala which must maintain employee performance. One of the factors that affect employee performance is work-life balance, and organizational commitment. This study aims to determine the effect of Work-Life Balance on employee performance mediated by employee organizational commitment at PT. BPR Santi Pala. The number of samples in this study is 36 respondents who are BPR employees. The analysis technique used is path analysis with the SPSS Ver 26 application. The results of this study found that Work life balance has a significant positive effect on employee performance. Work life balance has a significant positive effect on organizational commitment Organizational commitment has a significant positive effect on employee performance. Work life balance has a significant positive effect on employee performance by being mediated by organizational commitment, increasing Work life balance and supported by good organizational commitment, it will further improve employee performance at PT. BPR Santi Pala. The suggestion for this study is to hold activities to improve teamwork, employees are able to manage working hours more effectively so that performance is better